2009
DOI: 10.1348/147608308x395213
|View full text |Cite
|
Sign up to set email alerts
|

Development of an early memories of warmth and safeness scale and its relationship to psychopathology

Abstract: Experiences of early childhood have a major impact on physiological, psychological, and social aspects of maturation and functioning. One avenue of work explores the recall and memory of positive or negative rearing experiences and their association with psychopathology measures. However, while many self-report studies have focused on the recall of parental behaviours this study developed a new measure called the early memories of warmth and safeness scale (EMWSS), which focuses on recall of one's own inner po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
181
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(203 citation statements)
references
References 34 publications
16
181
0
6
Order By: Relevance
“…It is a onedimensional scale. Original validation studies by Richter et al, (Richter et al, 2009) presented good internal consistency (α = .97) as well as in the Portuguese validations studies of this scale (α = .95) (Cunha et al, 2014). The reference values are accordingly to those suggested by Kline (2010) and Maroco (Maroco, 2010).…”
Section: Methodsmentioning
confidence: 89%
“…It is a onedimensional scale. Original validation studies by Richter et al, (Richter et al, 2009) presented good internal consistency (α = .97) as well as in the Portuguese validations studies of this scale (α = .95) (Cunha et al, 2014). The reference values are accordingly to those suggested by Kline (2010) and Maroco (Maroco, 2010).…”
Section: Methodsmentioning
confidence: 89%
“…The scale is one-dimensional; higher scores indicate the presence of positive and nurturing rearing experiences. Original studies by Richter et al 36 reported good internal consistency (alpha = 0.97), as did validation studies of the Portuguese version of this scale (alpha = 0.95). 37 In the current study, internal consistency was also very good (alpha = 0.95).…”
Section: Methodsmentioning
confidence: 91%
“…Early Memories of Warmth and Safeness ScaleAdolescent Version (EMWSS-A) 36,37 The EMWSS-A is a 21-item self-report scale that assesses retrospectively memories of experiences of warmth and affection during childhood. Each item is rated on a five-point Likert-type frequency scale (1 = rarely to 4 = most times).…”
Section: Methodsmentioning
confidence: 99%
“…The EMWSS_peers is a self-report questionnaire, with 12 items, adapted from the EMWSS [4], that aims at measuring the recall of peer-related positive early emotional and relational memories. Participants are asked to select the frequency of emotional experiences characterized by warmth, care, safeness, soothing and positive affection in their relationship with peers (e.g., "I felt safe and secure with my peers/friends" or "I felt part of the peer group that I valued"), using a 5-point Likert scale (0 = "No, Never" to 4 = "Yes, Most of the time").…”
Section: Early Memories Of Warmth and Safeness Scale -Peers Version (mentioning
confidence: 99%
“…In fact, literature has consistently demonstrated that early affiliative experiences, either positive or negative, seem to play an important role on physiological, psychological and social aspects of human development and functioning [4][5][6].…”
Section: Introductionmentioning
confidence: 99%